Biochemical Effect of Some Newly Synthesized Nitrogen Containing Heterocyclic Compounds on Rats - NIZAMUDDIN, S.; EHTESHAMUDDIN, S.; KUMARI, VANDANA (Asian Journal of Chemistry, 2010)
The present investigation is an endeavour to analyse the effects of some newly synthesized nitrogen containing heterocyclic compounds, viz., 6,7-, benzo-3,4-furano-5-oxo-azepine, 6,7-benzo-3,4-furano-5-oximino-azepine and 8-hydroxy-9-methoxy-11-oxo-morphanthridine on biochemical aspects of laboratory rats.